The Effect Of Let’s Learn Online Application To The Student’s Achievment In Writing Descriptive Text - Siahaan, Mungkap Mangapul; Napitupulu, Selviana; Haloho, Uci Nursanty; Marbun, Lastri Evati Mori (Jurnal Ilmu Sosial Mamangan, 2024)
This research aims to determine the effect of the let's learn online application on student learning achievement in writing descriptive texts. This research is a type of quantitative research using a quasi-experimental design. This research used two groups; experimental and control groups. This is to find out which groups are effective to use in helping students achieve writing skills. In the experimental group the author provided treatment by teaching writing using let's learn videos in 38 lessons entitled "he is my best friend", while in the control group the author taught using conventional learning. Data were analyzed using Paired sample t-test. The results of this research are that there is an influence of using the let's learn online application on students' learning achievement in writing descriptive texts. The score of the experimental class students who used the let's learn video was 16.111 higher than the control class who were not treated.